Pengaruh Penggunaan Gadget terhadap Kualitas Ibadah - Innas Mutiah; Syamsiah Depalina Siregar (Jurnal Pendidikan dan Humaniora Rumbio, 2026)
This study aims to determine the extent to which gadget use affects the quality of worship among university students and adolescents in Indonesia. The habit of intensive gadget use changes the way individuals carry out daily activities, including worship. The method used was quantitative, with a questionnaire distributed to Muslim students in Indonesian universities and adolescents in several educational communities. The results of the statistical analysis showed a variation in gadget use from low to high, while the quality of worship, both in terms of time discipline and devotion, showed significant differences between groups that used gadgets wisely and those that did not. Several quantitative indicators such as frequency of timely worship, level of concentration in worship, and frequency of interruptions during worship were analyzed using linear regression. The research findings indicate that gadget use contributes to the quality of worship, but is also influenced by other factors such as religious motivation and spiritual self-control. Based on these results, it can be concluded that gadget use has a complex influence on the quality of worship. Uncontrolled use tends to decrease the quality of worship, while use integrated with prayer reminders and religious materials can have a positive effect on worship practices. These findings have important implications for education, families, and religious communities in guiding young people to be able to use technology wisely in the context of religious life.